Qualitative Study Of Indonesian High School Students’ Strategies In Academic Major Decision Making - Ragwan Mohsen Alaydrus; Nik Suryani Nik Abd Rahman (Universitas Islam Negeri Raden Mas Said Surakarta, 2022)
Educational decision making can be a challenging process for senior high school students. There are research reports investigated Indonesian high school students who perceived that they have taken wrong major decisions. This problem demands special attention from educators and school counselors to figure out the condition that gives rise to the phenomenon. This qualitative case study explored experiences of Indonesian high school students in academic major decision making. The purpose of this paper is to present an in-depth information about high school students’ strategies in educational planning process. Five students from three public high schools in Indonesia participated in this study. Qualitative data were collected from individual interviews and analyzed using thematic approach. The study identified four strategies of major decision making: reflecting on experiences, engaging in information-seeking, considering alternative majors, and compromising aspirations. The findings highlight the need to provide a comprehensive support for systematic educational exploration and decision making.